On-site financial costs of soil erosion by runoff from the Mizewa catchment of the Blue Nile basin - Taye, G.; Adgo, E.; Erkossa, Teklu (International Livestock Research Institute, 2013)
This study was conducted in Mizewa watershed which is located in Blue Nile Basin (BNB) to estimate on-site financial cost of erosion in terms of yield reduction taking maize as representative crop. For this purpose, discharge measurement and runoff sampling was made during the rainy season of 2011 at the outlet of three sub watersheds within Mizewa catchment; lower Mizewa (MZ0), Upper Mizewa (MZ1) and Gindenewur (GN0). The samples were filtered to separate the sediment which was subsampled for determination of suspended sediment concentration (SSC), sediment fixed NO3 -, NH4 + and available phosphorous (P) contents. The filtered water was used to assess dissolved nitrate and dissolved phosphate. The on-site financial cost of erosion was estimated based on productivity change approach (PCA) focusing on available NP losses. The result revealed that the SSC and its NP content varied in space and time, in which higher and lower SSC occurred towards the beginning and end of the rainy season, respectively. The mean seasonal discharge was found to be 2.12±0.75, 1.49±0.52 and 0.57±0.20 m3/ sec at MZ0, MZ1 and GN0 stations in that order while the corresponding sediment concentration was 510±370 mg/l, 230±190 mg/l and 370±220 mg/l. This led to the total suspended sediment loss (SSL) of 4 ton/ha/year, 2 ton/ha/year and 3 ton/ha/year from the respective subwatersheds. The on-site financial cost due to N and P lost associated with SSL was estimated to be USD 200/ha, USD 186/ha and USD 227/ha from MZ0, MZ1 and GN0 watersheds, respectively. The study revealed that the economic impacts of soil erosion which is variable based on the characteristics of land resources and management practices are immense and deserve due attention. The result may help in sensitizing both farmers and decision-makers about the risk of soil erosion and in targeting management practices to overcome the challenges.